An Update on Masked Hypertension - Anstey, D. Edmund; Pugliese, Daniel; Abdalla, Marwah; Bello, Natalie A.; Givens, Raymond; Shimbo, Daichi (Current hypertension reports, 2017)
Masked hypertension refers to the phenomenon of having a non-elevated clinic blood pressure (BP) despite having an elevated out-of-clinic BP. Masked hypertension is a common phenotype with a cardiovascular risk profile similar to that of sustained hypertension, defined as elevated clinic and out-of-clinic BP. Current guidelines offer little guidance on the best practices for detecting and treating masked hypertension. This is in part due to insufficient evidence upon which to base recommendations as many questions remain regarding the optimal clinical management of masked hypertension. In this review, we will discuss the recent literature on masked hypertension related to disease prevalence, diagnosis, screening strategies, adverse outcomes, and treatment, and will highlight critical areas for future research.